2022
DOI: 10.3389/fpsyg.2021.807546
|View full text |Cite
|
Sign up to set email alerts
|

Family and Psychosocial Functioning in Bipolar Disorder: The Mediating Effects of Social Support, Resilience and Suicidal Ideation

Abstract: Patients with bipolar disorder (BD) may experience family dysfunction, which might result in worse psychosocial functioning through environmental and psychological factors. Research investigating the mediating role of social support, resilience and suicidal ideation on family and psychosocial functioning in BD is rare. The study aims to explore the predicting and mediating effects of social support, resilience and suicidal ideation on family and psychosocial functioning in BD patients. Two hundred forty-six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Many different types of traumas have been found to cause PTSD, bipolar disorder, and manic disorder [ 26 , 27 , 28 , 29 ]. These types, and the proportion of PTSD, bipolar disorder, and manic disorder cases they make up, include the following: Sexual relationship violence—33% (e.g., rape, childhood sexual abuse, intimate partner violence).…”
Section: Discussionmentioning
confidence: 99%
“…Many different types of traumas have been found to cause PTSD, bipolar disorder, and manic disorder [ 26 , 27 , 28 , 29 ]. These types, and the proportion of PTSD, bipolar disorder, and manic disorder cases they make up, include the following: Sexual relationship violence—33% (e.g., rape, childhood sexual abuse, intimate partner violence).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to specialist interventions such as pharmacotherapy and psychotherapy, social support can also effectively support mental health. The adverse effects of BD include impairment of psycho-social functioning and a high risk of suicidal ideation [42]. Those with BD who lack social support or are socially isolated are at higher risk of relapse and suicidal ideation [43,44].…”
Section: Social Supportmentioning
confidence: 99%
“…Family caregivers should be educated and informed about mental health, and the community should be helped to develop a greater awareness of "mind, body and spirit" and the ways and means to cope with psychological problems. Emphasis should also be placed on strengthening social support while addressing skills and interpersonal practices, and addressing irrational cognitive patterns and cognitive biases (Dou et al, 2021).…”
Section: Mediating Effect Of Anxiety and Depressionmentioning
confidence: 99%
“…In addition, it has been found that social functioning and interpersonal/family relationships are highly correlated with the domains of relapse risk of suicide (McIntyre et al, 2022). People with SMI who have family dysfunction, which may be affected by environmental and psychological factors, leading to disease deterioration, and there is a bidirectional correlation between family function and psychosocial function (Dou et al, 2021). Given the results of the current findings, no single factor has been found to fully explain suicidal intention.…”
Section: Introductionmentioning
confidence: 99%